(untitled) (Nigerian Journal of Physiological Sciences, 2020)
The challenges associated with adequate deployment of nucleic acid amplification tests (NAATs) in developing countries underscores the important role of simple but sensitive and specific serological testing kits in COVID-19 diagnosis. Presently, there are a number of point-of-care tests for Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2) screening. However, the reliability of these test kits is poorly documented and hence, needs to be ascertained. This study was therefore designed to determine the sensitivity and specificity of two serological test kits for COVID-19 screening with the view to providing necessary information on the suitability of their deployment as routine test kits for SARS-CoV-2 in Nigeria. Forty-seven (47) asymptomatic adults who had been tested for SARS-CoV-2 with the real-time reverse-transcriptase polymerase-chain reaction (RT-PCR) were enrolled into this study. Blood samples were obtained for qualitative determination of serum IgM and IgG antibodies to the S-antigen of SARS-CoV-2 using a commercially available IgM and IgG Rapid Diagnostic Test (RDT) and enzyme linked immunosorbent assay (ELISA). The association between the test kits (ELISA and RDT) and PCR in diagnosing COVID-19 was determined using the Fisher’s Exact test at P<0.05. The sensitivity and specificity of the test kits were determined using ROC while the Positive Predictive Value (PPV), Negative Predictive Value (NPV), Positive Likelihood Ratio (PLR), Negative Likelihood Ratio (NLR), Diagnostic Odds Ratio (DOR) and accuracy were calculated as appropriate. Twenty-eight (59.6%) of the study participants had positive PCR result. ELISA and RDT identified 20 (42.6%) and 13 (27.7%) participants respectively as having anti- SARS COV-2 specific antibodies. ELISA had a better sensitivity performance, NPV, PLR, DOR and accuracy than the RDT while the RDT had a better specificity performance than ELISA. The proportion of participants with anti-SARS-CoV-2 IgM antibody identified using ELISA was significantly higher compared with RDT. In contrast, the proportion of participants with positive anti- SARS COV-2 IgG antibody identified using RDT was significantly higher compared with ELISA. ELISA has a better sensitivity for detecting anti-SARS-CoV-2 Spike-protein specific antibodies than the RDT. However, combination of RDT and ELISA for the detection of anti-SARS-COV-2 antibodies might be useful for population COVID-19 screening